Efeito do treinamento físico militar em recrutas ao longo do primeiro ano no exército - Collazo, Camila Charquero (2019)
The Brazilian military service is mandatory for the young men. The selected personnel must work for at least one year in the institution. Initially, they receive basic military training consisting of physical training, tactical training and work activities. Considering the importance of military physical training on the performance of recruits, in order to perform well during required military service associated with the small number of studies that analyzed the performance of soldiers in long training period, the aim of this study is to verify if the year of mandatory military service produces changes improvement in musculoskeletal variables of recruits. This is an observational, longitudinal, prospective, descriptive and quantitative research. The study sample was obtained by convenience, composed of healthy individuals, recruited for compulsory military service in the 6th Esquadrão de Cavalaria Mecanizada of Santa Maria / RS. Lower extremity dominance and physical activity level (International Physical Activity Questionnaire and Tegner Index) were collected at the time of start of military service. In addition, functional tests were performed to evaluate flexibility (sitting and reaching test), ankle range of motion (Lunge test), strength (manual dynamometry of knee extensors and abductors and lateral hip rotators) and power (Hop Test and Side Hop Test) of lower extremities before beginning of physical military training. The tests were repeated after 16 and 28 weeks of training. Repeated measures ANOVA was used for the statistical analysis, using the Mauchly test and Bonferroni post-hoc sphericity test for each of the variables of physical activity level, flexibility, ankle range of motion, strength and lower extremity power. The study sample was composed by 43 recruits, with a mean age with a mean age of 18.26±0.44 years, weight of 71.44±14.99kg, height of 1.71±0.07m and Body Mass Index of 24.40±4.55 kg/ m². 37 recruits (86.05%) of the sample showed right lower extremity dominance. Regarding the IPAQ, 64.29% of the sample had a high level of physical activity, 19.05% had a moderate level and 16.67% had a low level of physical activity. The average Tegner Index was 4.07±1.89. The participants showed an significant improvement in the anterior power of the dominant lower extremity from the first evaluation (121.33±24.74m) to the second (131.80±28.70m), but showed a significant decrease in the anterior power of both lower extremities from the second evaluation to the third (119.35±24.40m; p <0.03). In the lateral power of the lower extremities, the recruits showed improvement from the first evaluation (18.34±7.32s) to the second (13.50±5.70s) and from the second to the third (12.72±5.41s; p<0.05). About the isometric strength, the recruits showed improvement in both tests performed and in both dominant and non-dominant lower extremities after 16 and 28 weeks of Military Physical Training (p <0.01). In conclusion, the year of compulsory military service was able to produce significant improvement in the assessed musculoskeletal variables of strength, and power of lower in army recruits, especially after 28 weeks of physical military training.